PnTx2-6 (or δ-CNTX-Pn2a), a toxin from Phoneutria nigriventer spider venom, releases l-glutamate from rat brain synaptosomes involving Na+ and Ca2+ channels and changes protein expression at the blood-brain barrier. (August 2018) - Silva, Carolina Nunes da; Lomeo, Rosângela Silva; Torres, Fernanda Silva; Borges, Marcia Helena; Nascimento, Marta Cordeiro; Rodrigues Mesquita-Britto, Maria Helena; Rapôso, Catarina; Pimenta, Adriano Monteiro de Castro; da Cruz-Höfling, Maria Alice; Gomes, Dawidson Assis; de Lima, Maria Elena
Abstract: PhTx2 is the most toxic fraction from the venom of the spider Phoneutria nigriventer, being responsible to sodium entry into cortical synaptosomes, increasing the release of neurotransmitters, such as l -glutamate (L-Glu) and; acetylcholine. In this study, we investigated the action of a toxin purified from; PhTx2 fraction, called PnTx2-6 or δ-CNTX-Pn2a, on L-Glu release from rat; brain cortex synaptosomes, as well as its ability to induce blood-brain barrier permeability. PnTx2-6 increased L-Glu release from rat cortical brain synaptosomes in a time- and dose-dependent manner (EC50 = ∼20 nM; Tm = 16min), as measured by a fluorimetric method. The increase of L-Glu by PnTx2-6 was inhibited by tetrodotoxin. And partially inhibited by EGTA. Calcium channel blockers ω-conotoxin MVIIC (P/Q-types) and ω-conotoxin GVIA (N-type), were able to reduce the PnTx2-6-induced release of L-Glu, while nifedipine (L-type) did not show any inhibition. These findings suggest that thew release of L-Glu by PnTx2-6 is due its primary action on sodium channels, well-known to be target of this toxin. PnTx2-6 is able to potentiate penile erection and this effect may be related with the release of l -glutamate from the CNS, besides a local effect on corpus carvenosum, as previously shown by our group. If L-Glu release and penile erection potentiation are indeed correlated, then this toxin should be able to cross the blood brain barrier (BBB). Results by immunoblotting assays indicated a change in the expression of proteins associated with the paracellular and transcellular transport at the blood-brain barrier, suggesting a BBB dysfunction mediated by PnTx2-6. Therefore, PnTx2-6 may induce the release l -glutamate in the central nervous system, when injected peripherally. Graphical abstract: Image 1 Highlights: The toxin PnTx2-6 (or δ-CNTX-Pn2a) induces L-Glu release from rat brain synaptosomes. The L-glu release depends on Na + channels and P/Q and N Ca + channels. PnTx2-6 modifies proteins of blood brain barrier and should be able to cross it.